Computational modeling of polymer composites : a study of creep and environmental effects - Roy, Samit (CRC series in computational mechanics and applied analysis., 2014)
"This book provides a better understanding of the theories association with finite element models of elastic and viscoelastic response of polymers and polymer composites. Based on the authors original work in the subject area during the last three decades, it covers computational modeling of polymers and polymeric composites. It begins with a review of mathematical preliminaries, equations of anisotropic elasticity, then presents finite element analysis of viscoelastic materials and the diffusion process in polymers and polymeric composites. The book provides a reference for engineers and scientists and can be used as a textbook in graduate course